Willingness to pay for marine conservation of Tun Sakaran Marine Park, Semporna, Sabah, Malaysia - Latiff, Norasilah (2016)
Tun Sakaran Marine Park, Semporna, Sabah (TSMP) is a marine conservation area located in the water of Sulu Sea,Semporna, Sabah, Malaysia. Located in the Coral Triangle area that spans from Malaysia to the Solomon Islands, TSMP is rich in marine biodiversity. These resources have been attracting tourists to TSMP for many years.TSMP was gazetted as a Marine Park in 2004 and currently managed by Sabah Parks.Since the establishment, the statistics show increasing visitor arrivals. There is no entrance fee to TSMP, tourist are only required to pay for the jetty fee, which is RM2 for domestic tourists and RM10 for foreign tourists. This study is aimed to determine the values of marine conservation in TSMP by assessing the willingness to pay of tourists (WTP). In addition, the study also determined the factors influencing tourists’willingness to pay for marine conservation in TSMP. Contingent Valuation Method (CVM) was employed to elicit the values of WTP. The determination of these values directly represented the actual values of TSMP area in Ringgit Malaysia (RM). From the monetary value, level of awareness amongst tourists towards conservation program can be illustrated. Another significant contribution is that the estimated WTP suggested a range of preferred price for conservation fee TSMP from tourists’ perspective. Data was collected in series of face-to-face surveys. A total of 305 useable questionnaires were obtained and used in the analysis. The respondents were 18 years old and above towards tourists visited TSMP. The questionnaire comprised of four main structures which were visitation characteristic, measurement of satisfaction level, WTP and sociodemography.Using the Dichotomous Choice format, six level of bids amount were provided. The Ordinary Least Square Regression (OLS) analysis was conducted to determine the WTP model values by using the Statistical Package for Social Sciences(SPSS). The findings of the OLS analysis were founded 4 variables significantly influencing the values of WTP. Next, from the results of OLS analysis used to conduct the WTP model.The findings of the analysis showed that, most of the tourists are willing to pay for marine conservation towards 4 dimensions.There are (RM1.351 number of educational year), (RM3.662 Motives of visits: Business and Professional),ii(RM2.555 Characteristic of site: Variety of Recreational Activities) and (RM2.187 Gender). The WTP (CS) value for marine conservation in TSMP is RM1.887 per person/ visit/year. From this, it was found that, most of the TSMP tourists were concerned on marine conservation program. Otherwise, this showed that the tourists were willing to pay to maintain the quality of natural resources in TSMP.The findings of this study will be useful for the park management to making decision for the applicable of conservation fee in TSMP. Other than that, it will help the management park to improve the quality of managing towards to control tourists’ behaviour in TSMP area.